2020
DOI: 10.1073/pnas.2009531117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical design of the highly porous cuttlebone: A bioceramic hard buoyancy tank for cuttlefish

Abstract: Cuttlefish, a unique group of marine mollusks, produces an internal biomineralized shell, known as cuttlebone, which is an ultra-lightweight cellular structure (porosity, ∼93 vol%) used as the animal’s hard buoyancy tank. Although cuttlebone is primarily composed of a brittle mineral, aragonite, the structure is highly damage tolerant and can withstand water pressure of about 20 atmospheres (atm) for the species Sepia officinalis. Currently, our knowledge on the structural origins for cuttlebone’s remarkable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 57 publications
2
69
0
1
Order By: Relevance
“…The material's plastic property is given by the relationship between the plastic stress (MPa) and corresponding plastic strains: 350, 0; 368.71, 0.001; 376. 5 12. All four models are meshed using wedge and tetrahedral elements, with about 180 000 elements for each case.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material's plastic property is given by the relationship between the plastic stress (MPa) and corresponding plastic strains: 350, 0; 368.71, 0.001; 376. 5 12. All four models are meshed using wedge and tetrahedral elements, with about 180 000 elements for each case.…”
Section: Methodsmentioning
confidence: 99%
“…[ 3,4 ] Previous studies have suggested that cuttlebone's remarkable damage tolerance and high stiffness can be attributed to its characteristic “wall‐septa” internal morphology. [ 5 ] Several previous studies on cuttlebone have explored its potential applications by exploiting its chemical, structural, and mechanical characteristics as a natural cellular material. For example, cuttlebone itself can be used as a filler in natural rubber [ 6 ] and acrylic bone cement, [ 7 ] the mechanical properties of which are comparable to commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25,32,33 ] The role of the aragonite crystallites has been demonstrated to enhance strength, damage tolerance, and toughness, and the organic content also plays an important role in the improved damage resistance. [ 34 ] Based on these observations, we hypothesize that the rationally manipulated lamellae structure plays an important role in the fracture mechanism of cuttlebone.…”
Section: Figurementioning
confidence: 99%
“…These phenomena can be understood by the different deformation mechanisms: compression/stretching-dominated deformation mechanism and the bending-dominated deformation mechanism. [10,16,34] Kelvin foam is a typical bending dominated structure, which usually experiences uniform deformation under compression. Although such a deformation behavior is beneficial to avoid catastrophic failure, it sacrifices the strength and modulus of the structure.…”
mentioning
confidence: 99%
“…These evolutionary processes frequently act both independently and synergistically, resulting in characters that exhibit multifunctionality (3)(4)(5)(6). While classical characters, particularly those that have been employed for trait-based taxonomic purposes, typically represent macroscale features such as the size and shapes of bird beaks (7), species-specific characters (or phenotypes) also exist at the "material level" as nano-and microstructures (8)(9)(10)(11)(12). These micro-and nanoscale architectures have evolved to enable specific and diverse biological functions including, for example, mechanical protection and optical appearance (10,(13)(14)(15).…”
mentioning
confidence: 99%